Riometer data for: Characterizing auroral absorption based on geomagentic hourly range - Fiori, Robyn (Harvard Dataverse, 2020)
Level 3 1-second data files for the Natural Resources Canada (NRCan) riometer stations located at Cambridge Bay (CBB), Baker Lake (BLC), Iqaluit (IQA), Yellowknife (YKC), Meanook (MEA), and Sanikiluaq (SNK) for 2015-2017. Data fields include time, observed voltage (V), number of samples per second, voltage range per second (V), calibration flag (0-data period, 1-calibration period), quiet day curve voltage (V), absorption (dB), quality flag (1-good quality).